Home range, population density, habitat preference, and survival of fishers (Martes pennanti) in eastern Ontario - Koen, Erin Leanne (University of Ottawa (Canada), 2006)
By the 1940s, fishers (Mustelidae, Martes pennanti) were extirpated in Ontario south of the French and Mattawa Rivers, probably as a result of overharvesting and habitat loss. However, during the last several decades fishers have recolonized much of their former range in Ontario. This recolonization, combined with (for the most part) conservative harvest management, has led to increases in abundance. Perhaps inevitably, these increases have resulted in requests by fur harvesters to increase fisher quotas. The question then arises as to what the effect of the current quota system is on fisher populations in eastern Ontario. Unfortunately, very little is known about fisher demographics in eastern Ontario; as a result, the current management system is based almost exclusively on information and data on well-studied fisher populations from other regions, notably Algonquin Park. The extent to which these data---and the inferences regarding effective management therefrom---reflect fisher population characteristics in eastern Ontario is unknown.
Keywords: Biology, Ecology.; Biology, Zoology.